Teaching Innovation via Muhadharah to Enhance Rhetoric and Soft Skills - Kholifah, Alda Eky Nur; Agustin, Maulid (Institut Darul Falah Bandung Barat, 2025)
This study aims to analyze and describe teaching innovations through the muhadharah method in improving rhetorical competence and soft skills of students at Islamic High School Model Zainul Hasan Genggong, Probolinggo. A qualitative approach with a case study method is used to explore the implementation of muhadharah activities in depth, starting from planning, implementation, to evaluation. The results of the study indicate that muhadharah, which is implemented systematically through two main models Muhadharah Kubro and Sugro is able to improve public speaking skills, critical thinking, self-confidence, and interpersonal skills of students in a bilingual context (Arabic and English). The role of teachers as facilitators, motivators, and innovators has proven crucial in assisting students through script guidance, performative training, and the use of artificial intelligence (AI)-based technology. These findings confirm that the integration of the muhadharah method in the learning process is able to form students who are communicative, adaptive, and ready to face global challenges. Thus, muhadharah becomes a contextual, effective, and relevant learning strategy in the development of modern Islamic education.